Membranoproliferative glomerulonephritis in a patient with chronic brucellosis - Simella Provatopoulou; Marios Papasotiriou; Evangelos Papachristou; Hariklia Gakiopoulou; Markos Marangos; Dimitrios S. Goumenos (The Korean Society of Nephrology, 2018)
Brucellosis is the most common zoonotic disease in Greece, with an endemic distribution and can affect any organ. Infiltration of the renal parenchyma causes acute and chronic interstitial nephritis with granulomas, whereas renal glomeruli are rarely affected. The disease has been sporadically reported, and it causes various histopathologic patterns. Herein, we describe the case of a 39-year-old stock breeder with a history of recurrent episodes of bacteremia caused by Brucella melitensis over a period of 3 years. Two months after the last episode of bacteremia, he presented with mild renal insufficiency, nephrotic range proteinuria, and microscopic hematuria. A renal biopsy revealed membranoproliferative glomerulonephritis with a pattern of focal-segmental nodular sclerosis and moderate tubulointerstitial fibrosis. The patient received antimicrobial and corticosteroid therapy with partial remission of the nephrotic syndrome.